Cardiac protection of wogonin in mice with pulmonary fibrosis by regulating Sirt1/ γ-H2AX pathway - Wang, Libo; Lin, Fei; Miao, Runran; Zhao, Tianhao; Liu, Yuan; Yang, Lin; Zhang, Min (Frontiers in Pharmacology, 2025)
BackgroundClinical evidence suggests that pulmonary fibrosis (PF) and heart failure (HF) often co-exist; however, the specific impact of PF on HF remains underexplored. This gap in understanding complicates the management and treatment of HF in patients with PF.ObjectivesTo investigate the effects of PF on cardiac function and myocardial fibrosis using a mouse PF model and evaluate the therapeutic potential of wogonin, a flavonoid compound known for its anti-PF properties.MethodsA PF mouse model was established via intratracheal administration of bleomycin (BLM). Starting on day 8 post-BLM treatment, wogonin (50 mg/kg) was intraperitoneally administered every 2 days for 2 weeks. Cardiac function was assessed using echocardiography, while myocardial fibrosis was evaluated through Masson staining. In vitro, H9C2 cardiomyocytes were exposed to CoCl2 or H2O2 for 24 h with or without wogonin (20 μM) treatment. Apoptosis and DNA damage markers were analysed using immunofluorescence, immunoblotting, and the Comet assay. The interaction between wogonin and Sirt1 was examined using biotin-affinity pulldown assays and molecular docking simulations.ResultsMice with PF exhibited significant cardiac dysfunction and myocardial fibrosis. Wogonin treatment markedly improved ejection fraction and attenuated myocardial fibrosis in PF mice. Mechanistic studies revealed that wogonin alleviated DNA damage and cardiomyocyte apoptosis by upregulating Sirt1 and downregulating γ-H2AX expression. Docking simulations predicted that wogonin forms a stable complex with Sirt1 through hydrogen-bonding and hydrophobic interactions, which was further validated by biotin-affinity pulldown assays.ConclusionWogonin exerts protective effects against cardiac dysfunction and fibrosis in PF mice by modulating Sirt1/γ-H2AX-mediated pathways to reduce DNA damage and apoptosis. These findings suggest the potential of wogonin as a therapeutic agent for managing HF associated with PF.